Curvas epidêmicas e o perfil de pacientes hospitalizados pela covid-19 em um município de tríplice fronteira - Kunkel, Merielly (2023)
With non-seasonal characteristics and rapid transmissibility, the pandemic caused by the new coronavirus reached all parts of the world at different times, and in border regions the spread of the disease was related to the movement of people. The study sought to identify the epidemic curves and analyze the epidemiological profile of patients hospitalized for COVID-19 in a triple border municipality. This is a descriptive and analytical study, with retrospective series data, carried out in Foz do Iguaçu, Paraná, located in the triple border area of Brazil, Paraguay and Argentina. During the period studied, four epidemic curves were found, with a total of 35,817 diagnosed cases and 2,927 patients hospitalized for COVID-19. Epidemiological weeks 8 to 11 of 2021, corresponding to the third epidemic curve, had the highest absolute frequencies of positive cases for COVID-19. The majority of hospitalized patients with COVID-19 were male, with values above 55% on all curves. Cure was the most frequent option in curves 1, 2 and 4 (61.71%, 53.27% and 55.85%, respectively), however, without statistical difference (p= 0.2916). Curve 3 had a higher frequency of death (41.70%) compared to cure (38.77%). The mean age was significantly different among the curves (F= 21.2725; p< 0.0001), with higher age values observed in curves 1, 2 and 3 when compared to curve 4, which had the lowest mean age and was significantly different from the other three. The epidemiological analysis in the studied territory allowed us to identify that the dissemination of COVID-19 in the municipality occurred progressively until its apex in April 2021, the third curve. The progression may be related to the coping measures adopted by municipal managers, closure and opening of the International Friendship Bridge, vaccination, and behavior of the population regarding social isolation, especially in the younger age groups.